2004
DOI: 10.1016/s0736-0266(03)00155-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of patient age on human osteoblasts' response to Ti–6Al–4V implants in vitro

Abstract: Osseointegrated implants are a common therapy for the elderly population as lifespan increases. Understanding the effects of age and sex on osseointegration is important for successful implant therapy. Therefore, the response of primary human osteoblasts (HOB) to implant materials was studied. HOBs were obtained by outgrowth of cells from bone from orthopaedic procedures and categorized as Young (Y), <15; Middle (M), 30-50; and Old (0), >60 years old. Initially the HOB phenotype was determined on tissue cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 55 publications
5
41
0
1
Order By: Relevance
“…7,11,21 The resulting material is composed of approximately 99% tantalum and 1% vitreous carbon (by weight), has a pore size between 400 and 600 mm and porosity of approximately 80%. 14,22 TFM was prepared as discs 20 mm  1.7 mm (diameter  thickness) die-punched from sintered cpTi. TFM fabrication involves intertwining multiple cpTi fibers, sintering at high temperatures to weld fibers into a mesh structure.…”
Section: Substratesmentioning
confidence: 99%
See 4 more Smart Citations
“…7,11,21 The resulting material is composed of approximately 99% tantalum and 1% vitreous carbon (by weight), has a pore size between 400 and 600 mm and porosity of approximately 80%. 14,22 TFM was prepared as discs 20 mm  1.7 mm (diameter  thickness) die-punched from sintered cpTi. TFM fabrication involves intertwining multiple cpTi fibers, sintering at high temperatures to weld fibers into a mesh structure.…”
Section: Substratesmentioning
confidence: 99%
“…The first three passages were used for experiments. We have previously shown that more than 90% of these cells express alkaline phosphatase (ALP), an early marker of osteoblast progenitors, 14 and also over 80% of them express activated leukocyte cell adhesion molecule (ALCAM) which has been found in osteogenic precursors. 26 For mineralization, quantitative PCR and scanning electron microscopy (SEM), cells were cultured in the proliferation medium for 1 week, and for 2 more weeks in the differentiation medium of a-MEM, 10% FBS, 1% antibiotics, and 50 mg/ml of fresh ascorbic acid added daily.…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations